(untitled) (Journal of Academic Finance, 2022)
Objective: This study aimed to analyze the financial and social performance of Cameroonian Microfinance Institutions (MFIs). This specifically involved estimating performance scores and analyzing the explanatory factors underlying said performance. Methods: The data comes from MIX MARKET and covers 28 Cameroonian MFIs. The calculation of the performance scores is carried out from two models (financial performance (PF) and social performance (PS)) and uses the Data Envelope Analysis (DEA) method while the analysis of the determinants is made according to the bootstrap econometric model truncated. Results: The results of this study show that Cameroonian MFIs are generally less efficient (43.85%), this is due to the inefficiency observed at the financial level (49.48%). Clearly, the return on assets (2.7%) suggests that they have significant profitability compared respectively to that of MFIs in the Central African sub-region (- 0.6%), Africa in general (1.6%). However, the financial products fail to cover the charges. We also note that they have a very poor level of financial management with an average financial self-sufficiency ratio (95.3%). On the other hand, they have a very appreciable level of social performance (88.62%) Originality: These results constitute a plausible avenue of solutions to promote microfinance, the purpose of which is oriented towards the poor. Without, however, undermining their financial profitability, MFIs must put more emphasis on the fluidity and flexibility of the conditions allowing the poor to access financing. However, microfinance in its strategy should reconcile the objective of financial performance with that of social performance essential to ensure its sustainability. This strategy will further strengthen the achievement of its goal, which is to break the vicious circle of poverty into a virtuous circle of well-being so desired by the poorest.